1986
DOI: 10.3904/kjim.1986.1.1.21
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Study of Adult Japanese Encephalitis in the Chonnam District, Korea, During Summer of 1982 -A Difference between Improved and Expired Cases-

Abstract: In the summer of 1982, we experienced a great number of patients with Japanese encephalitis compared with the previous years. We have studied 85 adult cases of Japanese encephalitis which were diagnosed clinically and/or serologically. A difference between improved and expired cases was also investigated.We found that deteriorated mental state, elevated SGOT (AST) level, lower hemagglutination-inhibition(H-I) titer, and a more acute onset of the illness were associated with higher mortality.The mortality rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Whereas, less number of Japanese encephalitis/acute encephalitis syndrome in the adults (49/137, 35.8%) was likely due to the development of immunity, either by sub-clinical infections or by earlier vaccination [Sarkar et al, 2012c]. Similar to earlier studies, high grade fever was the common symptom in all the patients of both the age groups irrespective of their IgM positivity and RT-PCR positivity status [Bom et al, 1986;Kumar et al, 2006]. It has been observed that neck rigidity, convulsion and abnormal behavior were more likely to be present in the pediatricadolescent age group, whereas headache was found to be prominent in the adult age group, as reported by a recent study [Borah et al, 2011].…”
Section: Discussionsupporting
confidence: 80%
“…Whereas, less number of Japanese encephalitis/acute encephalitis syndrome in the adults (49/137, 35.8%) was likely due to the development of immunity, either by sub-clinical infections or by earlier vaccination [Sarkar et al, 2012c]. Similar to earlier studies, high grade fever was the common symptom in all the patients of both the age groups irrespective of their IgM positivity and RT-PCR positivity status [Bom et al, 1986;Kumar et al, 2006]. It has been observed that neck rigidity, convulsion and abnormal behavior were more likely to be present in the pediatricadolescent age group, whereas headache was found to be prominent in the adult age group, as reported by a recent study [Borah et al, 2011].…”
Section: Discussionsupporting
confidence: 80%
“…[18][19][20] Fever was the most common feature in adult and pediatric in the present as well as earlier studies. 21,9 Neck rigidity, convulsion, seizure and abnormal behavior were more likely to be present in children (P < 0.05), whereas both headache and myalgia were prominent in adult. In various studies, seizures and convulsion have been reported in only 10-15% of adult compared to 62.2-80% of children.…”
Section: Discussionmentioning
confidence: 99%
“…In various studies, seizures and convulsion have been reported in only 10-15% of adult compared to 62.2-80% of children. 10,11,17,[21][22][23] But in one comparative study between adult and pediatric reported seizure to occur more in adult (62.2%) than children (56.7%). 17 The abnormalities in liver and renal function in both adult and pediatric patients in the present study in accord with the information gathered in published papers.…”
Section: Discussionmentioning
confidence: 99%
“…Despite large variations observed in JE CFRs across time and space, currently there is no available country-specific CFR estimates for accurate mortality burden estimation. Reported JE CFRs were as low as 0% in Thailand in 1972[ 30 ], in Korea in 1982[ 31 ], in Japan in 1994[ 32 ], in India in 2004[ 33 ], and in Myanmar in 2013[ 34 ]. Reported JE CFRs were as high as 100% in Korea and India (estimates ranging from 1962–2006 [ 8 , 31 , 33 , 35 37 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Reported JE CFRs were as low as 0% in Thailand in 1972[ 30 ], in Korea in 1982[ 31 ], in Japan in 1994[ 32 ], in India in 2004[ 33 ], and in Myanmar in 2013[ 34 ]. Reported JE CFRs were as high as 100% in Korea and India (estimates ranging from 1962–2006 [ 8 , 31 , 33 , 35 37 ]).…”
Section: Introductionmentioning
confidence: 99%